Corn starch-based coating enriched with natamycin as an active compound to control mold contamination on semi-hard cheese during ripening - González Forte, Lucía Del Sol (2019)
The effectiveness of natamycin supported in corn starch-based films to control environmental molds (mainly Penicillium spp) activity that could colonize the surface of semi-hard cheese during ripening, was evaluated. The starch amount was maximized, and this was achieved by adding polyvinyl alcohol (PVA) and also polyurethane (PU) to the formulation. The PU acted as plasticizer and also provided functional groups that interacted with the natamycin and affected its diffusion. When 5 % PU was added, the natamycin migration of the coating doped with 1% natamycin was reduced by half. The natamycin distribution on both sides of the film was also evaluated, concluding that, in line with the reduced migration, when polyurethane is included, the formulation presents high hydrophobicity and natamycin is left with a preferential distribution towards the air face (exterior). For microbiological tests, microorganisms were isolated from cheese factories. Natamycin solutions showed inhibitory effect against environmental molds including Penicillium spp. Accordingly, films loaded with 0.1 % natamycin showed a significant inhibitory effect against Penicillium spp. The polymer combination in this work was optimized to obtain an active coating with good physicochemical properties and enriched with natamycin that has proven to be available for acting against molds and preferentially on the surface exposed to potential mold attack during ripening.